Oral hygiene status of individuals with cardiovascular diseases and associated risk factors - Divya Shetty; Mahima Dua; Kiran Kumar; Raghu Dhanpal; Madhusudan Astekar; Devi Charan Shetty (Clinics and Practice, 2012)
Dentist and oral health screening may be the latest weapon in identifying persons at risk of cardiovascular disease. Oral infections, specifically periodontitis, may confer independent risks for different systemic conditions. The risk factors associated with cardiovascular diseases also suggest that the relationship between periodontal disease and diabetes works in both ways. The aim of this study was to support and strengthen the association and relationship between oral hygiene status of individuals with cardiovascular diseases and its associated risk factors. A simple random sampling was carried out in 200 inhabitants of Western Utter Pradesh, India. An oral health visit and examination was made for an equal number of males and females of different age groups with cardiovascular diseases. Evaluation of the oral status was made by means of an oral hygiene index, community periodontal index of treatment needs and loss of attachment. Evaluation of oral status in patients with cardiovascular diseases and in the control group has shown a statistically significant low level of oral health in patients with cardiovascular diseases as compared to control. Prevalence of systemic diseases in different age groups significantly correlated with the prevalence of severe periodontal diseases. Treating gum disease may reduce the risk of heart disease and improve health outcomes for patients with periodontal disease and vascular heart problems.